274-LB: Complement Factor D Contributes to Metabolic Dysregulation by Hepatic CD9 Deficiency - ZHENG, YI (Diabetes (New York, N.Y.), 2023)
Diabetes-induced metabolic diseases involve functional integration among inter-organ communication, and the liver is central to this process. Here we show that deficiency of cell-surface protein tetraspanin CD9 in the liver of diabetic mice stimulates hepatocytes to synthesize and secrete complement factor D (CFD), which undermines whole-body metabolic homeostasis. Specifically, silencing liver CD9 exacerbated diet-induced obesity and fatty acid synthesis in white adipose tissue of mice with a markedly elevated CFD expression in both liver and plasma. Consistently, liver CFD-overexpressed mice exhibited severe hepatic steatosis, increased fat adipose deposition and decreased energy expenditure under HFD feeding. Mechanistically, CFD exerted its deleterious metabolic effects by activating its receptor C5aR-AKT dependent axis in the adipose tissues, and blockade of C5aR in adipocytes obviously abolished the CFD-induced lipogenesis and -suppressed thermogenesis in vitro and in vivo. Furthermore, we determined an increased CFD with the decreased CD9 expression in the fatty livers of human subjects, and also a negative correlation between CD9 and CFD was established in NAFLD patient samples. Together, these findings identify CFD inhibition as a potential pharmacological target for the management of diabetes and related metabolic disorders.